Impact of Video Describing Cataract Surgical Simulator Training on Patients' Perceptions of Resident Involvement in Cataract Surgery - Landis, Zachary C.; Fileta, John B.; Kunselman, Allen R.; Sassani, Joseph; Scott, Ingrid U. (Journal of Academic Ophthalmology, 2021)
Purpose The aim of this article is to investigate the impact of a 1-minute video describing resident training with a cataract surgical simulator on patients' perceptions regarding resident involvement in cataract surgery and to identify factors associated with patient willingness to have cataract surgery performed by a resident.Design Cross-sectional survey.Methods An anonymous Likert-style survey was conducted among 430 consecutive adult patients who presented for eye examination at the Penn State Health Eye Center. The survey included questions regarding demographics, understanding of the medical training hierarchy, and patient willingness to have a resident perform their cataract surgery. There were six questions regarding patient willingness to have residents perform their cataract surgery and the second question in this set informs the patient that residents are supervised by an experienced cataract surgeon. Patients were randomly assigned to one of two groups: patients in Group 1 completed the survey only, while patients in Group 2 watched a 1-minute video describing resident training with a cataract surgical simulator prior to completing the survey.Results Four hundred fourteen of the 430 patients (96.3%) completed the survey. Overall, 24.7% (n = 102) of respondents expressed willingness to allow an ophthalmology resident to perform their cataract surgery, and that proportion increased to 54.0% (n = 223) if the patient was informed that the resident would be supervised by an experienced cataract surgeon. Patients in Group 2 were twice as likely compared with patients in Group 1 to express willingness to allow an ophthalmology resident to perform their cataract surgery (odds ratio 1.92 [1.18–3.11], p = 0.009).Conclusions A thorough informed consent process including information regarding attending supervision and a brief video detailing resident training with a cataract surgery simulator may increase patient willingness to allow resident participation in cataract surgery.
Keywords: cataract surgical simulator; cataract surgery simulator; virtual reality; cataract surgery training; ophthalmology resident training